A RIGOROUS EXAMINATION OF THE APPROPRIATENESS AND CONSEQUENCES OF DEFERRED CORD CLAMPING IN PRETERM BABIES - BAKHT , F; NASIR , S; KAKAR , PK; HUSSAIN , U; ESSA , M; SHOIAB , U (Biological and Clinical Sciences Research Journal, 2023)
The timing of umbilical cord clamping is a pivotal decision in neonatal care, especially for preterm babies. Recent discussions have pivoted around the merits and drawbacks of Delayed Cord Clamping (DCC) compared to Immediate Cord Clamping (ICC). This study aimed to assess and contrast the implications of DCC versus ICC on clinical, respiratory, developmental, and maternal outcomes among preterm neonates. A multicentric, forward-looking, cross-sectional investigation was executed. The study encompassed 350 preterm neonates from various centers. They were categorically split: 175 underwent DCC, while the other 175 experienced ICC. Diverse outcomes, spanning clinical to maternal, were meticulously evaluated. DCC neonates demonstrated elevated early post-birth hemoglobin and hematocrit measurements. The DCC group reported reduced polycythemia occurrences, diminished transfusion necessities, and lesser demands for cardiovascular interventions. Regarding respiratory metrics, the DCC faction showed a decreased incidence of RDS. Neurodevelopmental indicators, such as cognitive and motor capabilities, were more pronounced in the DCC segment. The DCC group manifested reduced neonatal mortality rates and fewer sepsis cases. Maternally, post-delivery hemorrhage was comparable between groups, yet the DCC set displayed heightened satisfaction and a more pronounced initiation and continuity in breastfeeding. The evidence suggests that DCC may present multiple benefits over ICC for preterm neonates in terms of health and developmental outcomes. This underscores the potential of DCC as an integral component of best practices in neonatal care for premature babies.